2014
DOI: 10.4028/www.scientific.net/ssp.216.187
|View full text |Cite
|
Sign up to set email alerts
|

Stainless Steel Brackets: <i>In Vitro</i> Corrosion Behaviour and Mechanical Debonding Test

Abstract: The purpose of the study was to investigate the microchemical, morphological, mechanical and anticorrosive characteristics of the metallic brackets by using energy-dispersive X-ray spectroscopy (EDS), scanning electron microscopy (SEM), electrochemical and shear tests. The changes resulted from the exposure of the metallic brackets to artificial saliva and debonding forces were investigated under orthodontic appliances. The results have shown that metallic brackets studied in this paper present a good design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Metallic biomaterials such as stainless steel, magnesium, tantalum, titanium etc, have been widely used in many medical applications [1][2][3][4][5][6][7][8][9] for their good biocompatibility, good electrical conductivity, high strain energy (toughness), good wear resistance and outstanding combination of strength and ductility, compared with other materials. In terms of corrosion resistance, the most used metallic biomaterials are 316L stainless steel, Co-based alloys, and Ti-based alloy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metallic biomaterials such as stainless steel, magnesium, tantalum, titanium etc, have been widely used in many medical applications [1][2][3][4][5][6][7][8][9] for their good biocompatibility, good electrical conductivity, high strain energy (toughness), good wear resistance and outstanding combination of strength and ductility, compared with other materials. In terms of corrosion resistance, the most used metallic biomaterials are 316L stainless steel, Co-based alloys, and Ti-based alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of corrosion resistance, the most used metallic biomaterials are 316L stainless steel, Co-based alloys, and Ti-based alloy. Recent studies have shown that Zr-based alloys could be used as potential material for implants [2][3][4][5][6][7][8][9][10][11]. These characteristics along with relatively simple and common fabrication techniques (casting, forging, machining), or alternative conventional/advanced Powder Metallurgy techniques make metallic biomaterials suitable candidates for medical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation